THE CONCEPT OF RISK IN THE ACTIVITIES OF COMMERCIAL BANKS AND ITS ESSENCE - Khujaxonova Sitora Baxtiyarovna; Tukhtabaev Jamshid Sharafetdinovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article describes the risks inherent in the activities of commercial banks and measures taken to reduce their impact. Scientific proposals and recommendations have also been developed to reduce the risks associated with credit risks while ensuring the financial security of commercial banks.